Semiconductor electrochemical study of the passivity limits of austenitic stainless-steel in H2S-containing brines. (19th May 2021) - Case, Raymundo
ABSTRACT: The objective of the study is to correlate the effects of temperature, H2 S and Cl − concentration on the passivity limits and the onset of localised corrosion in UNS S31603 stainless steel by evaluating the changes in the semiconducting behaviour exhibited by the passive layer. The study is accomplished experimentally by using a combination of direct and alternate current electrochemical methods to study the passive layer formed by the stainless steel, in equilibrium with a gas phase at 2.8 MPa (400 psi) containing up to 60% mol of H2 S (bal. CO2 ) at temperatures from 25°C and up to 150°C. The results obtained indicate that the decrease of the passive layer stability formed on the UNS S31603 stainless steel is consistent with the increase in the electron donor carrier density. This is observed as a consequence of the effect of temperature and the concentration of Cl − and H2 S. In this context, the Cl − content in the brine was found to exert a larger effect than the H2 S activity at constant temperature.